Prevalence of Malaria Parasitaemia among Febrile Nigerian Children with Severe Malnutrition in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Malnutrition and malaria are common in sub-Saharan Africa, and understanding the relationship between protein-energy malnutrition (PEM) and malaria is of great public health importance. Findings from studies evaluating associations between various forms of malnutrition and malaria have been contradictory. This study aimed to determine the prevalence of malaria parasitemia among malnourished children and its various determinants studied.Materials and Methods:This was a cross-sectional study. Ninety febrile children with severe PEM aged 6–59 months (44 males and 46 females) based on modified Wellcome classification were enrolled as subjects and; 90 febrile well-nourished children age and sex matched children as controls. Both subjects and controls were enrolled consecutively in the emergency pediatrics unit of Aminu Kano Teaching Hospital from May to October 2013. The diagnosis of malaria parasitemia was based on the identification of asexual parasites on microscopy after Giemsa staining.Results:The prevalence of malaria parasitemia was 72.2% in the subjects, this was significantly higher than 37.8% in the controls (OR = 4.28, CI = 2.29–8.02). Parasite density was 2122 μL (400–1821). Age, sex, and type of PEM had no significant effect on the prevalence of malaria parasitemia and parasite density (P> 0.05).Plasmodium falciparum(P. falciparum) was seen in all the positive slides.Conclusion and Recommendation:Malnourished children experience more malaria than well-nourished children. Based on the findings of this study malnourished children should have access to the use of insecticide treated nets (ITN) and commence on malaria chemoprophylaxis.